Sleep quality and chronic pain in community dwelling older adults: preliminary results - Silva, Celuane Oliveira; Brandão, Glaudson Sá; Lino, Maria Eduarda Moreira; Fonseca, Adriano L.; Silva, Marcos Mota; Oliveira-Silva, Iransé; Campos, Francisco K. R.; Silva, Anderson S.; Silva, Rubens A.; Oliveira, Luis V. F.; Brandão, Glauber Sá (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: The natural process of human aging causes biopsychosocial alterations, which can trigger chronic pain and poor sleep quality in older adults. Considering the high prevalence and possible association between these two clinical conditions, special attention from public health policies is necessary to provide quality aging. Objective: To verify if there is an association between chronic pain and sleep quality among older adults in the community. Methods: A quantitative, cross-sectional study on the association of chronic pain with the sleep quality among older people in the community. Participants were evaluated using the Pittsburgh Sleep Quality Index (PSQI); Visual Analog Pain scale; questionnaires of sociodemographic and clinical data, assessment of cognitive impairment through the Mini Mental State Examination, and anthropometric assessments. The data were submitted to descriptive statistics. The means between the groups of older people with and without chronic pain were compared using the Student's t test for independent samples and Pearson's correlation coefficient (r) was used to analyze the association of PSQI with pain intensity. Results: In total, 51 older women were included, with a mean age of 70 ± 8 years. The majority had a low level of education (52.9%), low financial income (64.7%), and chronic pain (56.9%). It was found that the older adults with chronic pain presented worse sleep quality when compared those without chronic pain and a moderate (r=0.595) and significant (p<0.01) correlation between sleep quality and the intensity of chronic pain was observed. Conclusion: Older adults in the community with chronic pain present worse sleep quality when compared to the older adults without pain. There is a strong correlation between the intensity of chronic pain and sleep quality in older adults; the greater the intensity of pain, the worse the sleep quality. Trial Registration: Registro Brasileiro de Ensaios Clínicos (REBEC) Identifier: RBR-3cqzfy